Cointegration analysis between economic growth and the number of granted patents based on the example of the German economy - Myszczyszyn, Janusz (Analiza kointegracji pomiędzy wzrostem gospodarczym a liczbą otrzymanych patentów, 2020)
The main purpose of the article was to use the Granger cointegration test to confirm the long-term relationship between the level of economic growth in Germany and the number of granted patents, including the so-called economically valuable patents. The empirical analysis was based on available statistical data on the level of economic growth (seven time series) and the number of patents received and valuable patents in the period 1872-1913. In addition to estimates of Pearson’s correlation coefficients, tests for checking the unit root: ADF and KPSS, were used. They indicated that all the analysed time series are integrated in the first stage I(1), which enabled the use of the Engle-Granger cointegration test. The obtained research results did not confirm the long-term correlation between the level of economic growth in Germany and the number of granted patents, including the so-called economically valuable patents.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 9, s. 87-99
Keywords: Engle-Granger cointegration; granted patents; economic growth of Germany